Gene Expression Profiles of Human Cerebral Organoids Identify PPAR Pathway and PKM2 as Key Markers for Oxygen-Glucose Deprivation and Reoxygenation - Iwasa, Naoki; Matsui, Takeshi K.; Iguchi, Naohiko; Kinugawa, Kaoru; Morikawa, Naritaka; Sakaguchi, Yoshihiko M.; Shiota, Tomo; Kobashigawa, Shinko; Nakanishi, Mari; Matsubayashi, Masaya; Nagata, Riko; Kikuchi, Sotaro; et al. (Frontiers in Cellular Neuroscience, 2021)
Ischemic stroke is one of the most common neurological diseases. However, the impact of ischemic stroke on human cerebral tissue remains largely unknown due to a lack of ischemic human brain samples. In this study, we applied cerebral organoids derived from human induced pluripotent stem cells to evaluate the effect of oxygen-glucose deprivation/reoxygenation (OGD/R). Pathway analysis showed the relationships between vitamin digestion and absorption, fat digestion and absorption, peroxisome proliferator-activated receptor (PPAR) signaling pathway, and complement and coagulation cascades. Combinational verification with transcriptome and gene expression analysis of different cell types revealed fatty acids-related PPAR signaling pathway and pyruvate kinase isoform M2 (PKM2) as key markers of neuronal cells in response to OGD/R. These findings suggest that, although there remain some limitations to be improved, our ischemic stroke model using human cerebral organoids would be a potentially useful tool when combined with other conventional two-dimensional mono-culture systems.